Baclofen destabilises breathing during sleep in healthy humans: A randomised, controlled, double‐blind crossover trial. Issue 4 (25th October 2020) - Straus, Christian; Teulier, Marion; Morel, Sébastien; Wattiez, Nicolas; Hajage, David; Giboin, Caroline; Charbit, Beny; Dasque, Eric; Bodineau, Laurence; Chenuel, Bruno; Straus, Nicolas; Attali, Valérie; et al.
Abstract : Aims: Periodic breathing is frequent in patients with severe heart failure. Apart from being an indicator of severity, periodic breathing has its own deleterious consequences (sleep‐related oxygen desaturations, sleep fragmentation), which justifies attempts to correct it irrespective of the underlying disease. Animal models and human data suggest that baclofen can reconfigure respiratory central pattern generators. We hypothesised that baclofen, a GABAB agonist, may thus be able to correct periodic breathing in humans. Methods: Healthy volunteers were exposed to hypoxia during sleep. Participants who developed periodic breathing ( n = 14 [53 screened]) were randomly assigned to double‐blind oral baclofen (progressively increased to 60 mg/d) or placebo. The primary outcome was the coefficient of variation (CoVar) of respiratory cycle total time considered as an indicator of breathing irregularity. Secondary outcomes included the CoVar of tidal volume, apnoea–hypopnoea index, sleep fragmentation index and ventilatory complexity (noise limit). Results: The analysis was conducted in 9 subjects after exclusion of incomplete datasets. CoVar of respiratory cycle total time significantly increased with baclofen during non‐rapid eye movement sleep (median with placebo 56.00% [37.63–78.95]; baclofen 85.42% [68.37–86.40], P = .020; significant difference during the N1‐N2 phases of sleep but not during the N3 phase). CoVar of tidal volume significantly increased during N1‐N2 sleep. The apnoea–hypopnoea index, sleep fragmentation index and ventilatory complexity were not significantly different between placebo and baclofen. Conclusion: Baclofen did not stabilise breathing in our model. On the contrary, it increased respiratory variability. Baclofen should probably not be used in patients with or at risk of periodic breathing.